Sosialisasi Penulisan Karya Tulis Ilmiah Bagi Guru MAN 11 Jakarta Selatan - Indra Cahya Firdaus; Agung Wijoyo; Sofyan Mufti Prasetiyo (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The socialization of scientific writing (KTI) for teachers aims to increase the competence and professionalism of teaching staff through an in-depth understanding of the importance of KTI in the world of education. This activity emphasizes various types of relevant KTI, such as scientific articles, research reports, textbooks and learning modules. Good writing techniques, including topic selection, research, abstract writing, language use, and KTI structure, are discussed comprehensively. Practical steps in compiling KTI, starting from formulating problems, conducting literature reviews, designing research methods, to writing and revising reports, are also explained. Challenges such as limited time, access to literature, and writing skills are identified, and solutions through time management, resource utilization, and training are proposed. It is hoped that this socialization can help teachers produce quality KTI that contribute to the development of knowledge and improve the quality of education. Support from the government, educational institutions and the academic community is very necessary to achieve this goal.